(3hSGhS GdHMK GdJQHhj aj GdLGeYGJ GdYQHjIs - (3GdCejf, YOfGfs ((3HjQhJs (3cdjI GdJQHjI aj GdLGeYI GddHfGfjI(B- (3HjQhJs, 2016)
(3JaMU gPg GdhQbI GdHMhK GdJQHhjI GdYQHjI ef LGfHjf(B: (3GdehGVjY hefGgL GdHMK(B. (3JJchf eGOI GdHMK ef YjfI ef GdOQGSGJ (B((3ebGdGJ hQSGFd eGLSJjQ hOcJhQGg(B) (3GdJj YGdLJ ehVhY GdeYdejf hGdefThQI Ydi bGYOI HjGfGJ THcI GdeYdheGJ GdYQHjI GdJQHhjI (B((3TeYI(B) (3eG Hjf GdYGejf (B2007 (3h (B2013. (3ef LgI GdehGVjY JHjf GdhQbI Cf GdOQGSGJ GdJQHhjI JYGdL bVGjG GdbWGY GdJQHhj hdcfgG JJHY GSJQGJjLjI GdJLfH(B: (3GdGHJYGO Yf GdHMK aj GdhbGFY GdJQHhjI PGJ GdMSGSjI GdSjGSjI(B. (3CeG HGdfSHI ddefgLjI aGdOQGSGJ GdJQHhjI JJHY YOOkG ef GdbhGdH, gj Ydi GdJhGdj GdJQjHjI GdeLQOI, GdeYjGQjI, hGdJWHjb(B. (3Ef SjWQI gPg GdbhGdH hgGeTjI GdfehPL GdJMdjdj JSeM HGdGSJfJGL HCf gfGc JbGdjO aj GdHMK GdJQHhj GdYQHj Jbhe Ydi fhYjf ef GdhSGhS(B: (3hShGS GdYGde GdeMGjO hhShGS GdaGYd GdGLJeGYj(B. (3GdebGd GdfeWj aj gPg GdJbGdjO jJSe HGdUaGJ GdJGdjI(B: (3eQGLYI TcdjI ddCOHjGJ Ydi WQjbI dRhe eG dG jdRe, aQVjGJ UaQjI, JMdjd EMUGFj MjK GdaQhb GdOGdI gj GdgOa GdCSei ddHMK, GdhUhd Edi JhUjGJ eYdheI eSHbkG(B. (3JNdU GdhQbI Edi Cf GdhXjaI GdaYdjI dHQGeL GdeGLSJjQ hGdOcJhQGg GdLGeYjI aj HdOGffG gj GdJfTFI GdGLJeGYjI, CcKQ eeG gj JWhjQ GdeYQaI(B.s
(3GdfhY (B: (3ebGds
Keywords: Educational Research; Recherche en Education; (3GdHMK GdJQHhjs